Mutu Pendidikan Era Revolusi 4.0 di Tengah Covid-19 - Miftahul Janna Akmal; Rustan Santaria (Journal of Teaching dan Learning Research, 2020)
Abstract[English]:This paper aims to obtain an overview of the quality of education in the revolutionary era 0.4 amidst Covid-19 which is full of great challenges, which require teachers and education observers to make and create new changes and paradigms facing the revolutionary era 4.0 amid the Covid-19 outbreak. Currently the world of education is one of the sectors that has been heavily affected by the Covid-19 outbreak, which has experienced a decline in quality which is the background for this research. Based on the goal of creating high quality education quality in achieving true educational success. This study uses a critical analysis method that produces several points including the importance of the role of teachers in dealing with education in the era of 4.0 which is all machine-driven. The defense of the role of teachers in facing the challenges of the 4.0 revolution amid the Covid-19 outbreak and the creation of a new paradigm for teachers in facing the era of the industrial revolution 4.0.Abstrak[Indonesia]:Tulisan ini bertujuan untuk memperoleh gambaran mengenai mutu pendidikan era revolusi 0.4 ditengah Covid-19 yang penuh dengan tantangan hebat, yang mengharuskan guru dan para pemerhati pendidikan untuk melakukan serta menciptakan perubahan dan paradigma baru menghadapi era revolusi 4.0 di tengah wabah covid-19.  Saat ini dunia pendidikan menjadi salah satu sektor yang terkena dampak besar dari wabah covid-19 mengalami penurunan kwalitas yang kemudian melatar belakangi penelitian ini. Berdasarkan tujuan untuk menciptakan mutu pendidikan yang berkualitas tinggi dalam mencapai keberhasilan pendidikan yang hakiki. Penelitian ini Menggunakan metode analisis kritis yang menghasilkan beberapa point diantaranya pentingnya peran guru dalam menangani pendidikan era 4.0 yang semua serba mesin. Pertahanan peran guru menghadapi tantangan revolusi 4.0 di tengah wabah covid-19 serta terciptanya paradigma baru bagi guru dalam menghadapi era revolusi industri4.0.